2018
DOI: 10.3168/jds.2017-13713
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecium WEFA23 from infants lessens high-fat-diet-induced hyperlipidemia via cholesterol 7-alpha-hydroxylase gene by altering the composition of gut microbiota in rats

Abstract: Enterococcus faecium WEFA23 is a potential probiotic strain from Chinese infants with the ability to decrease cholesterol levels. Aiming to explore the mechanism of E. faecium WEFA23 in lowering cholesterol in vivo, we examined the gene transcriptions related to cholesterol metabolism, the composition of bile acids in feces, the synthesis of trimethylamine N-oxide (TMAO) in liver, and the composition of the gut microbiota of rats. We found that E. faecium WEFA23 enhanced the synthesis of bile acids by promotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Gut colonization with methanogenic archaea reduced plasma TMAO levels and attenuated the burden of AS, with decreased area and fat content in the atherosclerotic plaques, in Apo E −/− mice fed a TMA-supplemented or high choline diet (Ramezani et al, 2018). Enterococcus faecium WEFA23 improved the diversity of the gut microbiota in rats fed a HFD and decreased TMAO production and cholesterol levels (Huang et al, 2018). In human clinical trials, a study of 90 individuals with atherosclerotic CV disease risk factors suggested that Lactofermented Annurca apple puree was an effective functional food that could effectively control plasma TMAO and HDL-C levels (Tenore et al, 2019).…”
Section: Potential Of Tmao As a Therapeutic Target In Asmentioning
confidence: 99%
“…Gut colonization with methanogenic archaea reduced plasma TMAO levels and attenuated the burden of AS, with decreased area and fat content in the atherosclerotic plaques, in Apo E −/− mice fed a TMA-supplemented or high choline diet (Ramezani et al, 2018). Enterococcus faecium WEFA23 improved the diversity of the gut microbiota in rats fed a HFD and decreased TMAO production and cholesterol levels (Huang et al, 2018). In human clinical trials, a study of 90 individuals with atherosclerotic CV disease risk factors suggested that Lactofermented Annurca apple puree was an effective functional food that could effectively control plasma TMAO and HDL-C levels (Tenore et al, 2019).…”
Section: Potential Of Tmao As a Therapeutic Target In Asmentioning
confidence: 99%
“…TMAO downregulates two cytochrome P450 enzymes, cholesterol 7 a-hydroxylase (cyp7A1) that is rate-limiting for bile synthesis, and sterol 27-hydroxylase that participates in diverting cholesterol into bile acids. Hence, it decreases recirculation into the intestine for absorption [70]. Ding et al (2018) showed that TMAO significantly lowers the total bile acid pool size in mice [69].…”
Section: Tmao Promotes the Etiological Mechanisms Of Cvd In Ramentioning
confidence: 99%
“…Consequently, enterococcal strains that produce this type of antimicrobial peptides are better equipped to establish themselves in the GIT of the host, to directly inhibit pathogens and to modulate the host's gastrointestinal microbiota [230]. The potential for selected enterococci toward modulation of the GIT microbiota in the host, when administered orally, has been demonstrated in animal models [231,232].…”
Section: Enterococci and Potential Health Benefits Of Dairy Productsmentioning
confidence: 99%
“…Albano et al [233] demonstrated that an E. lactis strain decreased the cholesterol concentration in broth and as part of a cheese adjunct culture, whereas oral administration of certain E. faecalis or E. faecium strains led to a significant decrease in serum cholesterol levels of hypercholesterolemic animal models [232,234]. In the case of E. faecium, cholesterol excretion was promoted; cholesterol degradation and transportation genes were up-regulated, while genes involved in cholesterol synthesis were down-regulated [234].…”
Section: Enterococci and Potential Health Benefits Of Dairy Productsmentioning
confidence: 99%